SOSIALISASI SISTEM TATA KELOLA SAMPAH DENGAN SARANA FLOWCARD DI TPA MRICAN KABUPATEN PONOROGO DALAM PRESPEKTIF MASYARAKAT SEKITAR: Sosialisasi Alur TPA Mrican untuk masyarakat sekitar - Wawan Trisnadi Putra; Aliyadi Aliyadi; Rizal Arifin; Rifky Irfan Nurcahyo; Uruqul Nadhif Zacky (JURNAL ABDIMAS DOSMA (JAD), 2026)
The challenge of waste management lies not only in the volume but also in the increasingly complex characteristics of the waste and the limited processing facilities. The Regency Government has carried out management efforts through the construction of the Mrican TPST, the operation of several 3R TPS sites, as well as educational campaigns such as the SAMTAKU (Your Waste, My Responsibility) program. However, there are several structural issues, including low community participation in waste sorting and the suboptimal use of location-based management guidelines. This study can provide information related to ongoing waste management and help every passerby and newcomer to the Mrican landfill area to understand and comprehend the proper procedures for effective and environmentally friendly waste management by placing flow cards at each point that can be read by people entering the area, The results indicate that the information is very helpful for the village government in explaining the management of waste in their surrounding area